2021
DOI: 10.47672/ejb.840
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Dengue virus in Host immune system and its genomic variation

Abstract: Dengue viruses are the most prevalent arthropod-borne viral diseases in humans, infecting 50-100 million people each year. Its serotypes are the most common causes of arboviral illness, putting half of the world's population at risk of infection. Because there is no vaccine or antiviral medicines, the only way to manage the disease is to reduce the Aedes mosquito vectors. DENV infection can be asymptomatic or cause a self-limiting, acute febrile illness with varying degrees of severity. High fever, headache, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…More than 500 antibiotics are discovered yearly; however, almost 60% are obtained from the soil, this thereby representing the most critical reservoir for novel antibiotics with pharmaceutical and biological activity [43]. An investigation by Sohail et al (2014) reported the antimicrobial potential of acetonitrile and nhexane extracts of the R. stolonifer against some fungal and bacterial pathogenic strains [44]. In this study, the acetonitrile extract of R. stolonifera inhibited several fungal pathogenic strains such as A. niger, A. oryzae, C. albicans, P. digitatum and F. oxysporum, and the bacterial pathogens P. aeruginosa, E. coli, S. aureus, S. aureus (methicillin-resistant) and S. aureus (vancomycin-resistant), more effectively than the n-hexane extract.…”
Section: Discussionmentioning
confidence: 99%
“…More than 500 antibiotics are discovered yearly; however, almost 60% are obtained from the soil, this thereby representing the most critical reservoir for novel antibiotics with pharmaceutical and biological activity [43]. An investigation by Sohail et al (2014) reported the antimicrobial potential of acetonitrile and nhexane extracts of the R. stolonifer against some fungal and bacterial pathogenic strains [44]. In this study, the acetonitrile extract of R. stolonifera inhibited several fungal pathogenic strains such as A. niger, A. oryzae, C. albicans, P. digitatum and F. oxysporum, and the bacterial pathogens P. aeruginosa, E. coli, S. aureus, S. aureus (methicillin-resistant) and S. aureus (vancomycin-resistant), more effectively than the n-hexane extract.…”
Section: Discussionmentioning
confidence: 99%